Age-induced aortic modifications are accompanied by alterations in the antioxidant defense system in female rats - Asad, Sabahat Binte; Qian, Xin; Wang, Jiao; Asad, Wajeeha; Gao, Qiang; Cao, Yang; Huang, Yujia; Bin Jardan, Yousef A.; Shah, Tawaf Ali; Wondmie, Gezahign Fentahun; Bourhia, Mohammed; Lu, Chunmei; et al. (Frontiers in Medicine, 2023)
Aging leads to significant structural and functional changes in blood vessels, which disrupt their normal function and impact cardiovascular health. Current research is actively exploring the NRF2 antioxidative pathway, recognizing its role in protecting cells by preserving their antioxidant defenses against damage. However, there has been limited exploration into the role of the NRF2 pathway in vascular aging.The primary objective of this study was to determine whether age-related changes in the aorta are associated with variations in the baseline levels of antioxidant enzymes, with a particular emphasis on how the NRF2 pathway operates in the aortic wall. To achieve this, a group of healthy aging female SD rats was compared with their younger counterparts. Various assessments were conducted, including measuring blood pressure, analyzing serum lipid profiles, examining aortic tissue, and assessing the expression of antioxidant enzymes.The results revealed significant differences in both blood pressure and serum lipid levels between the aged and younger rats. The examination of the aorta in older rats showed structural alterations, increased apoptosis, and the accumulation of fatty deposits. In the older rats, levels of SOD-1 (superoxide dismutase) and GSS (glutathione synthetase) were lower, whereas NRF2, KEAP-1 (Kelch-like ECH-associated protein 1), and HO-1 (Heme oxygenase 1) were higher.This study advances our understanding of how aging affects the antioxidant system in blood vessels, particularly in relation to the regulation of the NRF2/HO-1 pathway in the aorta.These findings suggest that targeting the NRF2/HO-1 pathway could present a novel therapeutic approach for addressing age-related vascular issues.